Utilization of Arbuscular Mycorrhizal Fungi and Coconut Shell Charcoal to Increase Gmelina arborea Roxb. and Ochroma bicolor Rowlee. Seedlings Growth in the Nursery - Sri Wilarso Budi; Tirsa Eka Saputri; Maman Turjaman (Jurnal Silvikultur Tropika, 2014)
Latosol has spread quite widely in Indonesia, but this soil was low fertility. The success rate of planting in latosol can be supported by species selection and high quality seedling. The improvement of seedlings quality can be carried out by the application of arbuscular mycorrhizal fungi (AMF) and coconut shell charcoal. The research was conducted in a greenhouse used split plot design with a completely randomized design. The results showed that the inoculations of Gigaspora sp give the best growth on G. Arborea seedling, while the inoculation of Glomus sp. Comined with charcoal 20 % give the best growth on O. Bicolor. . In general, inoculation of plant by Gigaspora sp. provided better response than Glomus sp. .